ANTIBACTERIAL POTENTIAL OF NANOENCAPSULATED CURCUMIN BY ELETROSPRAYING TECHNIQUE - AMITKUMAR P. PATEL; VIMAL M. RAMANI; TANMAY HAZRA; KUNAL M. GAWAI (The Journal of Research ANGRAU, 2024)
The study was undertaken during the year 2020–21 to study the nanoencapsulation of curcumin through electrospraying for embracing its ability as a nutraceutical and exploring possible health benefits. To facilitate nanoencapsulation process, electrospraying as a modern technique was used to coat curcumin as a bio-functional ingredient. Curcumin has been utilized for the treatment of several ailments due to its functional capacity and vast variety of medicinal, biological, and pharmacological qualities. Curcumin was encapsulated with zein protein and Tween 80 as coating materials in different combinations (Curcumin: Zein 1:10, 1:15, and 1:20 with 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1.0% and 1.5% Tween 80).This combination was studied for the particle size, zeta potential and concentration of nanoparticles along with morphological characteristics. The smallest particle size that was noticed was 250nm in 1:10 Curcumin: Zein with 0.4% Tween 80 combination with zeta potential of -7.51 ± 0.15 mV and concentration of nanoparticles was 5.94×108. Zein and Tween 80 coated curcumin (ZTC) nanoencapsulated powder showed a good antibacterial activity against gram-positive (Bacillus subtilis, Bacillus cereus, Staphylococcus aureus) and gram-negative (Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris) bacteria.